Potential of germinated brown rice and its bioactives as replacement for hormone therapy in menopausal model - Sani, Ismaila Muhammad (2014)
Menopause is a stage in a woman‘s life when her menstrual cycle ceases due to the gradual decrease of sex steroid hormone estrogen in circulation. Mood swings, hot flashes, bone and heart diseases are among the characteristic features that affect women in menopause. Currently, hormonal therapy (HRT) has been employed in the management of patients with menopausal disorders; however, HRT is associated with carcinogenicity and other related health problems. Germinated brown rice (GBR) contains antioxidants and bioactive compounds. In this study, GBR bioactive compounds were evaluated independently as potential agents to replace hormone therapy. The antioxidant effects of the GBR- Phenolics using various antioxidant assays were carried out, while ovariectomized rats were used as a model in-vivo. Results for the GBR-Phenolics antioxidant values showed a significant increase (p<0.05) in antioxidant values and the total phenolic content( TPC) and DPPH results when comparing neutral with acidic and basic catalysed hydrolysis samples,yield was slightly higher in acidic hydrolysis than in basic hydrolysis (p>0.05), with TPC and TFC being highest in acidic hydrolysis. A significant correlation was observed between ABTS and FRAP. Antioxidant activity using DPPH was higher in acidic medium, while the ABTS % scavenging activity and FRAP showed the highest values in basic hydrolysis. Bone density increases significantly (p<0.05) in rats treated with estrogen, GBR,remifemin and oryzanol compared to ovariectomized non-treated group. Histological section reveals more osteoblast in the treated groups compared with the un- treated groups; and a good correlation was obtained when results of bone densities obtained using Archimedes principle were compared with those obtained using the Edge detection technique between the treated groups. GBR and its bioactives, significantly increased the weight and length of both the uterus and the vagina than the OVX-non treated (p<0.05). Significant changes were observed in the ratio of cornified epithelial cells and number of leucocytes in the vaginal cytology between the oophrectomized and the treated groups. There was also an increase in the luminal and glandular epithelial cells activity in the treated compared with the un-treated groups histologically. Groups treated with GABA100 and 200 mg/kg showed significant up regulation of Sparc, Calcitonin and BMP-2 genes (p<0.05).While Oryzanol treated group at 200 and 100 mg/kg revealed significant (p<0.05) up-regulation of OSX,Postn, RUNX-2 and collagen 1&2. Similarly, IL-6 concentration decreased, while osteocalcin level increased significantly (p<0.05) in treated group as compared to ovariectomized non-treated groups. This study gives a clue in the management of menopause and associated post-menopausal metabolic complications using GBR and its related bioactive compounds.